Desenvolvimento de um método para determinação de Sb(III) e Sb total em amostra de interesse ambiental utilizando geração de hidretos acoplada à espectrometria de absorção atômica com chama - Néri, Thaís de Souza (2014)
In this work, a method for Sb(III) and total Sb determination of using NaBH4 reagent online with by generating hydrides atomic absorption spectrometry was developed. For the determination of Sb(III) variables such as sample flow-rate, flow-rate and concentration of HCl and NaBH4 were studied. For the determination of total Sb variables such as concentration and flow-rate of NaBH4 were studied to ensure direct analysis by hydride generation using online prereduction of Sb(V). The analytical frequency was 30 analyzes per hour and precision, relative standard deviation, for Sb(III) was 0.38% and for total Sb was 0.08%. The accuracy of the proposed method was evaluated by addition and recovery tests applied in water samples and analysis of certified materials (APS 1066 sediments and APS 1075 drinking water). Recovery tests were in the range of 98.8 103.7%. Limits of detection and quantification for determination of Sb(III) were 0.22 g L- 1 and 0.73 g L- 1 and the total Sb were 0.25 g L- 1 and 0.82 g L- 1, respectively. Finally, samples of seawater, algae, crustaceans and sediments of Ubatuba-SP were analyzed by the developed method.